Sains dan Teknologi Al Qur`an dan Implikasinya dalam Pendidikan - Octav, Istias; Nur Amelia, Safira; Syukri Azhari, Devi (UNIVERSITAS SERAMBI MEKKAH, 2025)
This abstract will discuss the importance of integrating Islamic religious education, science and technology in the context of modern education, especially through the perspective of the Koran. Islamic religious education which includes the teachings in the Koran provides a moral, ethical and spiritual basis in everyday life. On the other hand, science and technology have an important role in the development of knowledge and the advancement of civilization. The Qur'an itself contains many verses that encourage Muslims to think rationally, seek knowledge, and use the universe as a sign of God's greatness. The implication of Islamic religious education based on the Koran in science and technology education is to create a balance between spiritual and rational aspects, and encourage students to utilize knowledge and technology responsibly and ethically. It is hoped that education that combines the two can produce a generation that is not only intellectually intelligent, but also has strong character and cares about human welfare and environmental sustainability. Through this approach, it is hoped that an integration of science and faith will be created in facing global challenges in the modern era.